A Narrative Review of the Anti‐Hyperglycemic and Satiating Effects of Fish Protein Hydrolysates and Their Bioactive Peptides. Issue 21 (28th September 2020) - Sharkey, Shaun J.; Harnedy‐Rothwell, Pádraigín A.; Allsopp, Philip J.; Hollywood, Lynsey E.; FitzGerald, Richard J.; O'Harte, Finbarr P. M.
Abstract: Prevalence of type 2 diabetes and overweight/obesity are increasing globally. Food supplementation as a preventative option has become an attractive option in comparison to increased pharmacotherapy dependency. Hydrolysates of fish processing waste and by‐products have become particularly interesting in a climate of increased food wastage awareness and are rapidly gaining traction in food research. This review summarizes the available research so far on the potential effect of these hydrolysates on diabetes and appetite suppression. Scopus and Web of Science are searched using eight keywords (fish, hydrolysate, peptides, satiating, insulinotropic, incretin, anti‐obesity, DPP‐4 [dipeptidylpeptidase‐4/IV]) returning a total of 2549 results. Following exclusion criteria (repeated appearances, non‐fish marine sources [e.g., macroalgae], and irrelevant bioactivities [e.g., immunomodulatory, anti‐thrombotic]), 44 relevant publications are included in this review. Stimulation of hormone secretion, regulation of glucose uptake, anorexigenic potential, identified mechanisms of action, and research conducted on the most potent bioactive peptides identified within these hydrolysates are all specifically addressed. Results of this review conclude that despite wide methodological variation between studies, there is significant potential for the application of fish protein hydrolysates in the management of bodyweight and hyperglycemia. Abstract : This review summarizes fish protein hydrolysates (FPH) and their effect on blood glucose/obesity. Specific peptides in these FPH are also discussed. The results show that FPH are generally useful for lowering blood glucose and managing appetite. By addressing methodological issues, and if future studies focus on discovering mechanism of action, they could be useful for future nutritional interventions.